ONLINE BOOKSTORES AND WEBSITES FOR DEVELOPING LIBRARY COLLECTIONS FOR CHILDREN - Majid, Shaheen (Malaysian Journal of Library and Information Science, 2004)
In the past, the identification and selection of materials for children was a cumbersome task as adequate selection tools are expensive and difficult to obtain in developing countries. The Web has revolutionised the collection development process by providing access to up-to-date information about items, book reviews, and several other value-added features. This paper reviews websites of some selected online bookstores, publishers of children’s literature, libraries, and individual consultants, which can be used for selecting materials for children. It also provides an overview of the unique features of these websites, their browsing and searching capabilities, book selection tools and other value-added products and services. Online book shopping and order tracking capabilities of these websites are also discussed